The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s1519-38292006000300007
|View full text |Cite
|
Sign up to set email alerts
|

Disfunção familiar referida pela presença de depressão materna e/ou alcoolismo na família e ocorrência de cárie dentária em crianças de dois e três anos de idade

Abstract: OBJETIVOS: identificar a associação entre disfunção familiar, referida pela presença de alcoolismo na família e/ou presença de sintomas de depressão materna e a cárie dentária em crianças de dois e três anos de idade. MÉTODOS: a população consistiu de 74 famílias de Salvador, Bahia. A coleta de dados compreendeu o exame bucal das crianças e a entrevista com suas mães no domicílio. Foram utilizados para o diagnóstico de cárie dentária os critérios adotados pela da Organização Mundial de Saúde, classificando pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 15 publications
0
7
0
17
Order By: Relevance
“…Parental stress has been reported as a potential risk factor for caries in preschool children 14,17,18 , and parents' and caregivers' cognitive characteristics have also been associated with caries in this group 19 . Other psychosocial factors, like alcohol abuse in the family and maternal psychiatric disorders have been associated with this condition 14,15,16 . Quiñonez et al 18 also observed that severe early caries was associated with psychosocial alterations, as in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Parental stress has been reported as a potential risk factor for caries in preschool children 14,17,18 , and parents' and caregivers' cognitive characteristics have also been associated with caries in this group 19 . Other psychosocial factors, like alcohol abuse in the family and maternal psychiatric disorders have been associated with this condition 14,15,16 . Quiñonez et al 18 also observed that severe early caries was associated with psychosocial alterations, as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial factors represent a group of determinants that can influence the behavioral attitudes and biological mechanisms directly involved in the etiopathogenesis of early caries. This influence may occur through psychological processes, capable of interfering in the family's capacity to care for the developing child 6,16 , or through biological processes, since psychosocial factors in the family setting can trigger stressful phenomena, resulting in immune alterations, like a reduction in the production of specific antibodies 18 , which can contribute to the appearance of caries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the idea that mental health can have an impact on oral health and that mothers are the main caregivers during childhood, studies have been assessing the relationship between maternal mental disorder and children's oral health . Maternal mental problems may lead to a family dysfunction, inadequate care, and a negative effect on mother‐child interactions that could affect oral health of their offspring …”
Section: Introductionmentioning
confidence: 99%